Inhibition of Enveloped Viruses Infectivity by Curcumin - Chen, Tzu-Yen; Chen, Da-Yuan; Wen, Hsiao-Wei; Ou, Jun-Lin; Chiou, Shyan-Song; Chen, Jo-Mei; Wong, Min-Liang; Hsu, Wei-Li (PloS one, 2013)
Curcumin, a natural compound and ingredient in curry, has antiinflammatory, antioxidant, and anticarcinogenic properties. Previously, we reported that curcumin abrogated influenza virus infectivity by inhibiting hemagglutination (HA) activity. This study demonstrates a novel mechanism by which curcumin inhibits the infectivity of enveloped viruses. In all analyzed enveloped viruses, including the influenza virus, curcumin inhibited plaque formation. In contrast, the nonenveloped enterovirus 71 remained unaffected by curcumin treatment. We evaluated the effects of curcumin on the membrane structure using fluorescent dye (sulforhodamine B; SRB)-containing liposomes that mimic the viral envelope. Curcumin treatment induced the leakage of SRB from these liposomes and the addition of the influenza virus reduced the leakage, indicating that curcumin disrupts the integrity of the membranes of viral envelopes and of liposomes. When testing liposomes of various diameters, we detected higher levels of SRB leakage from the smaller-sized liposomes than from the larger liposomes. Interestingly, the curcumin concentration required to reduce plaque formation was lower for the influenza virus (approximately 100 nm in diameter) than for the pseudorabies virus (approximately 180 nm) and the vaccinia virus (roughly 335 × 200 × 200 nm). These data provide insights on the molecular antiviral mechanisms of curcumin and its potential use as an antiviral agent for enveloped viruses.